Innovation in entrepreneurship during the time of COVID-19: a scoping review of the scientific evidence from Peru [version 1; peer review: 1 approved, 2 approved with reservations] - Sofía Almendra Alvarado-Suyo; Giovanni Di Deus Ocupa-Meneses; Johanna de Jesús Stephanie Gago-Chávez; Hitler Giovanni Ocupa-Cabrera; Josefina Amanda Suyo-Vega; Rosario Violeta Grijalva-Salazar; Víctor Hugo Fernández-Bedoya; Monica Elisa Meneses-La-Riva (F1000Research)
Background: Entrepreneurship involves the actions of designing, launching and managing a business that initially starts small and grows along with the human structure that integrates it.  The health crisis caused by coronavirus disease 2019 (COVID-19) had negative effects on health, but also on business; many ventures had to innovate in order to survive in this uncertain environment. Peru is a country located in Latin America, recognized for its high levels of entrepreneurial self-efficacy, so this scooping review sought to identify the experiences of innovation in entrepreneurship in times of COVID-19 in that country. Methods: We explored the Scopus and Scielo databases for records detailing innovation in entrepreneurship in both English and Spanish. Inclusion and exclusion criteria were: published between March 11, 2020, to May 5, 2023; English, Spanish, and Portuguese language; original articles that present both quantitative and qualitative results; within Peru; articles with an assigned issue and volume number. The search results identified 5 Peruvian experiences that met the research objectives. Results: The records identified deal with innovations in social entrepreneurship, women's entrepreneurship, entrepreneurship in the educational sector, and new business tools applied during the COVID-19 pandemic. The sources where these records were disclosed were South American journals (3 cases) and conference proceedings (2 cases). The language of the articles was recorded, identifying that most of them are written in Spanish (official language of Peru). Conclusions: We recommend the regional scientific community to disseminate the results of their research in scientific journals indexed in high-level databases in order to have greater visibility.